Faktor Ekonomi Dan Ketimpangan Wilayah Kawasan Timur Indonesia - Abd Hakim Aflaha; Zulgani; Rosmeli (Program Studi Ekonomi Syariah, Fakultas Ekonomi dan Bisnis Islam, Universitas Al Hikmah Indonesia, 2026)
Regional development disparities remain a major issue in Eastern Indonesia (KTI). Despite possessing significant natural resource potential, economic development across provinces in KTI shows a considerable gap compared to Western Indonesia. This disparity is reflected in differences in income levels, the quality of human resources, local fiscal capacity, and the distribution of investment across regions. This study aims to: (1) analyse the level of inter-provincial regional development inequality in Eastern Indonesia; (2) analyse the level of intra-regional development inequality between districts/cities in Eastern Indonesia; and (3) analyse the influence of the Human Development Index, Fiscal Decentralisation, and Foreign Direct Investment on regional development inequality in Eastern Indonesia. Secondary data for the period 2010–2024 were analysed using multiple linear regression within a panel data framework via the EViews 14 application, with inequality measured using the Williamson Index and the Theil Index.The results of the Williamson Index reveal significant variations in disparity across provinces. Gorontalo falls into the low inequality category, Bali and several provinces in Sulawesi into the moderate category, whilst West Papua and Papua fall into the very high category. The results of the Theil Index show that Central Sulawesi and West Nusa Tenggara have the highest levels of intra-regional inequality, whilst Gorontalo and West Sulawesi have relatively low levels. Estimates from the selected Random Effects Model indicate that the HDI has a negative and significant effect on inequality as measured by the Williamson and Theil indices. DESF has a non-significant negative effect in the Williamson model, but a significant positive effect in the Theil model. Furthermore, FDI has a positive and significant effect on inequality as measured by the Williamson and Theil indices